Religious Awareness and Ecological Meaning in Rote Folklore: The Story of Aman Lailonda Bay - Niftrik Enklaar Tanau (Asian Journal of Applied Education (AJAE), 2026)
This study examines the functions and meanings of the Rote folk tales, “Teluk Aman Lailonda” and “Hak Aman Nepe Dae,” which embody local wisdom. The objective is to analyze their religious, moral, and ecological values, as well as their relevance to contemporary society. The study employs a qualitative method with a descriptive-interpretive approach through a literature review of texts recorded by F. H. van de Watering (1921) and translated by Ebenhaizer I. Nuban Timo. The analysis is based on the folklore theories of Alan Dundes and James Danandjaja, as well as Mircea Eliade’s concepts of the sacred and the profane. The results of the study indicate that these stories emphasize humanity’s dependence on transcendent forces, the importance of humility, work ethic, integrity, and ecological awareness. These stories serve as a medium for character education and the transmission of cultural values relevant to addressing moral and environmental crises.